Ogyu Sorai's Philosophical Masterworks : the Bendo and Benmei - Tucker, John A. (Honolulu : University of Hawaii Press, 2006)
Ogyu Sorai (1666-1728) was one of the greatest philosophers of early modern Japan. This volume, a monumental work of scholarship, offers for the first time in any Western language unabridged and fully annotated translations of Sorai's masterpieces. The Bendo (Distinguishing the Way) and Benmei (Distinguishing Names) are works of political philosophy that define the theoretical foundation for a leadership exercising total power, the best remedy, in Sorai's view, for a regime in crisis. The translations are based on the 1740 (Genbun 5) woodblock edition, the first major edition of these seminal texts published during the Tokugawa period. In his commentary, John Tucker situates the Bendo and Benmei in relation to Neo-Confucianism via what is known as "philosophical lexicography." This genre, which links Sorai's thinking with Neo-Confucianism, is traced to the early-thirteenth-century Song dynasty text the Xingli ziyi (The Meanings of Neo-Confucian Terms) by Chen Beixi (1159-1223). Although Sorai was an unrelenting critic the Neo-Confucian formulations of the great Song synthesizer Zhu Xi (1130-1200), his thinking remained, due to its genre, methodology, and conceptual repertory, essentially a radical revision of Neo-Confucian discourse. Tucker's introduction also examines the reception of Sorai's two Ben during the remainder of the Tokugawa, calling attention to radical tendencies in later developments of Sorai's thought as well as to the increasingly scathing critiques of his "Chinese" approach to philosophy, language, and politics. Finally, it traces the vicissitudes of the two Ben in modern Japanese intellectual history and their role in the formation of the ideas of Meiji intellectuals such as Nishi Amane (1829-1897) and Kato Hiroyuki (1836-1916). As before, however, Sorai came under attack--this time for his supposed irreverence toward the throne, the Japanese people, and the imperial nation-state. Though an unpopular philosophy in early twentieth-century Japan, in the postwar years Sorai's thought was interpreted (by Maruyama Masao and others) as an important modernizing force. While it critiques such ideologically grounded attempts to cast Sorai's Bendo and Benmei as theoretical contributions to political modernization, Tucker's study nevertheless acknowledges that Sorai's masterworks, in their concern for language analysis as the way to solve philosophical problems, share significant common ground with the analytic approach to philosophy pioneered by various twentieth-century Anglo-American philosophers
Frontmatter -- Contents -- Series Editor's Preface -- Preface -- Acknowledgments -- Introduction to the Bendo and Benmei -- Chapter One: The Bendo and Benmei as Philosophical Dictionaries -- Chapter Two: The Fate of Kobunjigaku in Tokugawa Japan -- Chapter Three: Sorai in Modern Intellectual History -- Distinguishing the Way (Bendo) -- The Bendo -- Distinguishing Names (Benmei) -- Preface -- 1. The Way -- 2. Virtue -- 3. Humaneness -- 4. Wisdom -- 5. The Sages -- 6. The Rites -- 7. Ritual Principles -- 8. Filial Piety and Brotherly Deference -- 9. Loyalty and Trustworthiness -- 10. Empathy -- 11. Sincerity -- 12. Respectfulness, Reverence, and Carefulness -- 13. Humility, Deference, Obedience, and Not Boasting -- 14. Courage, Martial Arts, Strength, and Firmness -- 15. Purity, Scrupulousness, and Having No Desires -- 16. Regulations and Frugality -- 17. Impartiality, Correctness, and Straightforwardness -- 18. The Mean, Harmony, and Rectitude -- 19. Goodness -- 20. Originating, Flourishing, Advantageous, and Firm -- 21. Heaven, Fate, Lord-on-high, and Ghosts and Spirits -- 22. Human Nature, Human Feelings, and Capabilities -- 23. Mind, Purpose, and Ideas -- 24. Thoughts, Plans, and Calculations -- 25. Rational Principle, Generative Force, and Human Desires -- 26. Yin, Yang, and the Five Processes -- 27. The Five Constants -- 28. Ultimate Standards -- 29. Learning -- 30. Culture and Refinement, Substance and Function, and Roots and Branches -- 31. The Standard and Expediency -- 32. Things -- 33. Princes and Commoners -- 34. True Kings and Hegemons -- Notes -- Bibliography -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 24. Sep 2018).
JSTOR
Keywords: Ogyū, Sorai, -- 1666-1728.; Ogyū, Sorai, -- 1666-1728.; Bendō (Ogyū, Sorai); Philosophy, Confucian -- Early works to 1800.; Philosophie confucéenne -- Ouvrages avant 1800.; PHILOSOPHY -- Eastern; Philosophy, Confucian; Early works